Inulin Supplementation Reduces Systolic Blood Pressure in Women with Breast Cancer Undergoing Neoadjuvant Chemotherapy - Yizel Becerril-Alarcón; Saúl Campos-Gómez; Juan J. Valdez-Andrade; Karen A. Campos-Gómez; Diana Y. Reyes-Barretero; Alejandra D. Benítez-Arciniega; Roxana Valdés-Ramos; Alexandra E. Soto-Piña (Cardiovascular Therapeutics)
Introduction. Breast cancer is the most frequently diagnosed malignancy in women, and comorbidities like hypertension and obesity diminish their quality of life and negatively affect their response to chemotherapy. Furthermore, inulin supplementation is associated with the reduction of cardiovascular diseases (CVD) risk. Objective. To determine whether inulin supplementation prevents the elevation of blood pressure in women with breast cancer undergoing neoadjuvant therapy with cyclophosphamide and doxorubicin. Methods. This was a randomized, double-blind placebo controlled trial which included women with early-stage breast cancer undergoing neoadjuvant therapy (n=38). Patients were randomly assigned to participate in two different groups to receive either 15 g of inulin or 15 g of placebo (maltodextrin) for 21 days. Body composition and blood pressure were evaluated before and after the supplementation period. Results. Women in the inulin group showed a lower systolic blood pressure (SBP) after the supplementation (-4.21 mmHg, p<0.001). However, SBP increased in the placebo supplemented group. Diastolic blood pressure (DBP) nonsignificantly decreased in the inulin group. Inulin supplementation also increased BMI (p<0.001) but reduced BFP (p=0.288). Furthermore, confounding variables, such as BMI, baseline fasting glucose, age, menopause status, vomiting, constipation, and chronic medication did not have a statistical influence over the inulin effect on SBP. Conclusion. Inulin supplementation reduces SBP and prevents increases in DBP in women with breast cancer. This could be an innovative nutraceutical approach to prevent hypertension present in women with this type of cancer at an early stage and may improve the quality of life of the patients and their prognostic development through chemotherapy. Trial Registration Number. This trial is registered with ACTRN12616001532493.